Virulent duck enteritis virus infected DEF cells generate a unique pattern of viral microRNAs and a novel set of host microRNAs - Wu, Xianglong; Jia, Renyong; Zhou, Jiakun; Wang, Mingshu; Chen, Shun; Liu, Mafeng; Zhu, Dekang; Zhao, Xinxin; Sun, Kunfeng; Yang, Qiao; Wu, Ying; Yin, Zhongqiong; et al. (BMC veterinary research, 2018)
Background Duck enteritis virus (DEV) belongs to the family Herpesviridae and is an important epornitic agent that causes economic losses in the waterfowl industry. The Chinese virulent (CHv) and attenuate vaccines (VAC) are two different pathogenic DEV strains. MicroRNAs (miRNAs) are a class of non-coding RNAs that regulate gene expression in viral infection. Nonetheless, there is little information on virulent duck enteritis virus (DEV)-encoded miRNAs. Results Using high-throughput sequencing, we identified 39 mature viral miRNAs from CHv-infected duck embryo fibroblasts cells. Compared with the reported 33 VAC-encoded miRNAs, only 13 miRNA sequences and 22 “seed sequences” of miRNA were identical, and 8 novel viral miRNAs were detected and confirmed by stem-loop RT-qPCR in this study. Using RNAhybrid and PITA software, 38 CHv-encoded miRNAs were predicted to target 41 viral genes and formed a complex regulatory network. Dual luciferase reporter assay (DLRA) confirmed that viral dev-miR-D8-3p can directly target the 3’-UTR of CHv US1 gene ( p < 0.05). Gene Ontology analysis on host target genes of viral miRNAs were mainly involved in biological regulation, cellular and metabolic processes. In addition, 598 novel duck-encoded miRNAs were detected in this study. Thirty-eight host miRNAs showed significant differential expression after CHv infection: 13 miRNAs were up-regulated, and 25 miRNAs were down-regulated, which may affect viral replication in the host cell. Conclusions These data suggested that CHv encoded a different set of microRNAs and formed a unique regulatory network compared with VAC. This is the first report of DEF miRNAs expression profile and an analysis of these miRNAs regulatory mechanisms during DEV infection. These data provide a basis for further exploring miRNA regulatory roles in the pathogenesis of DEV infection and contribute to the understanding of the CHv-host interaction at the miRNA level.